FIRST REPORT FROM THE STATE OF RIO GRANDE DO SUL, BRAZIL ON CYLICOSPIRURA (CYLICOSPIRURA) FELINEUS (CHANDLER, 1925) SANDGROUND, 1932 (NEMATODA, SPIROCERCIDAE) IN LEOPARDUS GEOFFROYI D'ORBIGNY & GERVAIS, 1844 (CARNIVORA, FELIDAE) - Gallas, Moisés (2014)
In the Neotropical Region, the only species of Cylicospirura reported so far in felines is Cylicospirura (Cylicospirura) subaequalis in Paraguay and Brazil. Between 2007 and 2009, roadkilled specimens of Leopardus geoffroyi (n = 6) were donated for necropsy. Nematodes found in the stomach of one individual were identified as Cylicospirura (Cylicospirura) felineus by the presence of six large tricuspid teeth, a vulva anterior to the junction of the esophagus and intestine, and the size of the spicules. The prevalence of C. (C.) felineus in L. geoffroyi was 16.7%. No lesions caused by the nematodes were found in the infected feline, as reported in other studies. This is the first report of C. (C.) felineus in the Neotropical Region (State of Rio Grande do Sul, Brazil) and L. geoffroyi represents a new host.